Relevansi Ilmu Ushul Fiqh di Era Kontemporer - Ikhsan, Muhammad Miftahul; Akhiri, Yusuf Al (Lembaga Yasin AlSys, 2024)
Islamic law is used as a guide for Muslims in carrying out life, because Islam becomes a whole religion (kaffah) that regulates all aspects of life from small problems to big problems that exist according to the Qur'an and Sunnah. Shafi'iyah scholars explain that ushul fiqh is to look at the general legal basis by looking at its use as well as the person who performs ijtihad. This type of research uses literature research that takes data through information by obtaining library materials, data collection techniques for this research using documentation. data that has been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. One of the uses of ushul fiqh is to provide legal basis capital by using the method carried out by mujtahid in providing new problem solutions in accordance with syar'i. The science of ushul fiqh continues to undergo renewal in the contemporary era because the problems are increasingly numerous and diverse, various theories are used to express opinions or laws to be determined, such as Fazlur Rahman through the theory of the Double Movement, Other thoughts related to the relevance of ushul fiqh science in the contemporary era are that there is a method formed by Abu Zayd with Ta'wil theory. In the book mafhum by Abu Zayd, in describing the invisible meaning in the text. In the sense that both implied and express meanings in the content of the law are discussed in the method from Abu Zayd.